Synergistic Mechanism of an Ionic Liquid-Based Composite Surfactant-Stabilized Microemulsion for Effective Separation of Oily Sludge - Li, Xueshu; Li, Wenhao; Li, Qiuhong; Wang, Ruiyao; Lv, Cuiling; Ouyang, Zhiyi; Ou, Shengyong; Zhang, Bin; Wang, Shuai; Jiang, Haohan (ACS omega, 2025)
The reduction and harmless treatment of oily sludge are challenging tasks. As green solvents, ionic liquids (ILs) have been used to treat oily sludge effectively; however, their high price limits the applications. In this paper, an imidazolium-based IL 1-hexadecyl-3-methylimidazole chloride salt ([C16mim]Cl) was synthesized and compounded with Tween20 to obtain a composite surfactant that could be used as an emulsifier to prepare a microemulsion for the treatment of oily sludge. The composite surfactant exhibited the greatest synergistic effect at a mass ratio of 4:6. Under optimal conditions, the oil removal rate reached 94.90%, and the residual oil rate was reduced to 1.67%. Moreover, the microemulsion exhibited a high removal rate for asphaltenes (81.01%). The treatment mechanism and synergism were proposed based on a combination of interfacial tension (IFT) and quartz crystal microbalance (QCM-D) measurements. Herein, the π–π stacking and hydrogen bonds between S, N, and O in asphaltenes or resins and N atoms of imidazole rings in [C16mim]Cl were responsible for the effective treatment of the two components. The use of a microemulsion stabilized by a composite surfactant provided an efficient, environmentally friendly, and sustainable treatment method for oily sludge with high asphaltene and resin content.